Building the capacity builders: lessons from a multi-country training programme for local consultants. Issue 4 (19th May 2018) - James, Rick
ABSTRACT: Local consultants are an implicit, but overlooked, part of many capacity development strategies. It takes a trustworthy consultant to facilitate genuine change in a civil society organisation. This practical note identifies the learning from a local consultant formation programme ("Consultants for Change" – C4C) implemented in five countries in 2016–17. The note highlights six factors critical to C4C's apparent success: recruitment; focus of the learning; design of the process; assignments between modules; mentoring support; and the human/financial resources. These same factors may be relevant and applicable to other capacity development programmes.